2010
DOI: 10.1515/cclm.2010.123
|View full text |Cite
|
Sign up to set email alerts
|

Combined analysis of survivin autoantibody and carcinoembryonic antigen biomarkers for improved detection of colorectal cancer

Abstract: A positive association between autoantibodies against survivin and preoperative CEA concentrations in sera of patients with CRCs was established. Our results suggest that analysis of both parameters would assist in screening patients with CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 25 publications
1
21
1
1
Order By: Relevance
“…Rohayem et al (14) established a strict cutoff of the mean + 3 SDs and their data lead to a higher positivity when the cutoff was set as the mean + 2 SDs. Chen et al (18) established the cutoff using different criteria (Yowden's index from receiver operating characteristic curve analysis: sensitivity, +; specificity, -1); therefore, healthy volunteers exhibited a higher positivity rate (percentage of pseudo-positive patients, 35.9%) compared to the results of our study (8.1%; 5/62; actual plotting data not shown).…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Rohayem et al (14) established a strict cutoff of the mean + 3 SDs and their data lead to a higher positivity when the cutoff was set as the mean + 2 SDs. Chen et al (18) established the cutoff using different criteria (Yowden's index from receiver operating characteristic curve analysis: sensitivity, +; specificity, -1); therefore, healthy volunteers exhibited a higher positivity rate (percentage of pseudo-positive patients, 35.9%) compared to the results of our study (8.1%; 5/62; actual plotting data not shown).…”
Section: Discussioncontrasting
confidence: 50%
“…As regards the positivity of anti-survivin antibody, Rohayem et al (14) reported a relatively lower positivity rate (8.2%; 4/49) in patients with colorectal cancer using their ELISA protocol. By contrast, Chen et al (18) reported high positivity (sensitivity, 56.9%) in patients with colon cancer. This significant difference by different investigators is mainly attributed to the criteria for establishing a cutoff value.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Auto-Abs are highly specific, stable, and handily detectable in small volumes of specimens with well-established secondary reagents. These advantages lead many efforts into discovery of auto-Abs as biomarkers for detection of various types of cancers, such as colorectal (10)(11)(12), breast (13)(14)(15), ovarian (16,17), lung (18)(19)(20), liver (21,22), and pancreatic (23,24) cancers. As for OSCC, five auto-Abs have been individually identified as serum biomarker candidates, including anti-p53 (25)(26)(27)(28), anti-survivin (29,30), anticytokeratin 8 (CK-8; ref.…”
Section: Introductionmentioning
confidence: 99%
“…Tumors may, e.g., induce the formation of specific antibodies, such as antibodies against HER-2 in patients with breast cancer [72] . There are reports indicating that the detection of autoantibodies in patients with cancer could be useful diagnostically as demonstrated for anti-survivin antibodies in patients with colorectal cancer [73] . Interestingly, the presence of autoimmune response may be a positive prognostic factor, e.g., the presence of anti-thyroid peroxidase antibodies in patients with breast cancer [74] .…”
Section: Detection Of the Host Response Against Tumormentioning
confidence: 99%